Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1756-3305-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Present and future potential of plant-derived products to control arthropods of veterinary and medical significance

Abstract: The use of synthetic pesticides and repellents to target pests of veterinary and medical significance is becoming increasingly problematic. One alternative approach employs the bioactive attributes of plant-derived products (PDPs). These are particularly attractive on the grounds of low mammalian toxicity, short environmental persistence and complex chemistries that should limit development of pest resistance against them.Several pesticides and repellents based on PDPs are already available, and in some cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 111 publications
1
76
0
4
Order By: Relevance
“…Our studies showed neem extract has better insect control than Bt. Neem extract has insecticidal activity to a wide range of insects (George et al, 2014). Resende et al (2016) indicated that the richness and diversity of insects depend on location and insecticide spray.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies showed neem extract has better insect control than Bt. Neem extract has insecticidal activity to a wide range of insects (George et al, 2014). Resende et al (2016) indicated that the richness and diversity of insects depend on location and insecticide spray.…”
Section: Discussionmentioning
confidence: 99%
“…The observed mortality of ticks may be accounted by several possible mechanisms working separately or working in synergic (Chandler ., 2011;Kunz & Kemp, 1994). In some cases, insecticides can have both insecticidal and acaricidal properties (George ., 2014). It is believed that the mechanism of action of terpenoids and f lavonoids might be similar to that of the organophosphate compounds.…”
Section: Effects Of Commiphora Swynnertonii Exudates On Tick's Abilitmentioning
confidence: 99%
“…Senyawa organik yang berasal dari mimba mudah menguap, dilaporkan sebagai komponen insektisida, terdiri atas 6-betahydroxygedunin, nimbin, dan triterpenoid salannin (22,23-dihydronimocinol dan desfurano-6-alphahydroxyazadiradione) yang berasal dari daun segar. Meliacin (7-alfa-senecioyl-(7-deacetyl) -23-o-methylnimocinolide) dan meliacinol [24,25,26,27-Tetranorapotirucal-la-(apoeupha) -1-alphatrimethylacryloxy-21, 23-6-alpha, 28-diepoxy-16-oxo-17-oxa-14,20,22-trien-3-alpha, 7-alpha-diol] dari batang dan kulit kayu (George et al 2014). Senyawa organik yang mudah menguap dari tanaman mimba adalah monoterpen yang bersifat racun bagi serangga dan jamur patogen (Holopainen dan Blande 2013).…”
Section: G100h Dan Slnpv Telah Dilaporkan Sebelumnya Olehunclassified